The Influence of the Project-Based Learning Integrated Ethno-STEM of Chemical Equilibrium on the Pancasila Student Profile Mutual Cooperation Dimension - Akhmad Masrukhan Nur; Sudarmin, Sudarmin; Kasmui, Kasmui; Susilaningsih, Endang (Universitas Negeri Semarang, 2024)
The character of mutual cooperation has not been widely applied in the implementation of Pancasila Student Profile character education. The research aims to analyze the influence of the project-based learning integrated Ethno-STEM on the Pancasila Student Profile Mutual Cooperation Dimension. The research method was carried out using a true-experiment pretest-posttest control group design. Data collection instruments include an observation sheet for the Pancasila Student Profile Mutual Cooperation Dimension and a questionnaire for student responses to the project-based learning integrated Ethno-STEM in the Pancasila Student Profile Mutual Cooperation Dimension. Data analysis techniques include validity testing, reliability testing, testing the difference in the average value of each indicator, and testing the average value of each statement. The results of the research concluded that (a) the Pancasila Student Profile Mutual Cooperation Dimension assessment instrument that had been developed was declared very feasible and reliable, (b) the comparison of the average observation scores for each indicator of the Mutual Cooperation Dimension experimental class was higher than the control class shows that PjBL-Ethno-STEM can improve mutual cooperation attitudes, (c) the average student response strongly agrees with the project-based learning integrated Ethno-STEM is applied to provide the Pancasila Student Profile Mutual Cooperation Dimension.